The influence of wind and basin geometry on surge attenuation along a microtidal channel in the western Baltic Sea - Joshua Kiesel; Arne Knies; Athanasios T. Vafeidis (Cambridge Prisms: Coastal Futures)
The capacity of river mouths to reduce storm surge water levels upstream, referred to as along-estuary attenuation, has been assessed by several studies. The coastal protection function of semi-enclosed water bodies such as lagoons and channels with narrow inlets remains less explored and generalization is hampered by differences in morphology and hydrodynamic forcing. Here we use a hydrodynamic model to investigate surge attenuation along a microtidal channel with a narrow inlet at the Baltic Sea coast of Germany called The Schlei. We quantify the importance of wind and the contribution of the barrier spit system, which is constricting the inlet, to the reduction of water levels at the landward end of the channel. In addition, we explore the role of dikes in the region for the reduction of peak water levels and coastal flooding. We find effective along-channel attenuation inside The Schlei in its current state, which is mostly a result of the channel’s narrows. However, reduction rates decrease under simplified sea-level rise scenarios. Furthermore, along-channel attenuation is highly variable and can change to substantial amplification depending on hydrometeorological forcing. The barrier spit contributes to along-channel attenuation whereas the effect of existing dikes (or their removal) for along-channel attenuation is negligible.